Performance Analysis of Energy Detection Based Spectrum Sensing with Unknown Primary Signal Arrival Time - Wu, Jwo-Yuh; Wang, Chih-Hsiang; Wang, Tsang-Yi (IEEE transactions on communications, 2011)
Spectrum sensing in next-generation wireless cognitive systems, such as overlay femtocell networks, is typically subject to timing misalignment between the primary transmitter and the secondary receiver. In this paper, we investigate the performance of the energy detector (ED) when the arrival time of the primary signal is modeled as a uniform random variable over the observation interval. The exact formula for the detection probability is derived and corroborated via numerical simulation. To further improve the detection performance, we propose a robust ED based on the Bayesian principle. Computer simulation confirms the effectiveness of the Bayesian based solution when compared with the conventional ED.